PENGARUH MEDIA PEMBELAJARAN VISUAL TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN GEOGRAFI DI UNIVERSITAS PGRI PALEMBANG TAHUN AKADEMIK 2016/2017 - Boby Agus Yusmiono (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
Abstract, As a teacher we need an appropriate learning medium. The use of instructional media will help lecturers to create a conducive learning environment so that the student activeness increases in the end of student learning outcomes will achieve the expected learning outcomes. This research method using experimental method, used to find effect of treatment (treatment) certain to other in controlled condition. Based on the result of the research to the students, it can be seen that the students who were given treatment (treatment) by using visual learning media get the average value (post-test) of 82,50 whereas before the students who tdiberikan treatment (treatment) using visual learning media only get value average (pre-test) equal to 74,70, there is difference of mean value equal to 7,90. So it can be concluded that the learning process on semester students 5.B in the subject of Political Geography of ethnographic materials, using visual learning media gives positive contribution to student learning outcomes. Keywords: Visual Learning Media, Learning Outcomes